Types of Diastolic Dysfunction of the Left Ventricle in Adolescents with Myocardial Pathology - L.F. Bogmat; V.V. Nikonova; E.L. Akhnazaryants; T.S. Vvedenskaya; S.R. Tolmacheva; L.I. Rak; T.A. Golovko (Zaslavsky O.Yu., 2014)
In adolescents with myocardial pathology during isometric tests we detected three types of diastolic dysfunction of the left ventricle (LV) of the heart, depending on E/A ratio. The most pronounced signs of diastolic filling disorders were detected in the third group of patients, as evidenced: by a tendency to increase isovolumic relaxation time, a significant increase of slowing down time of the first phase of left ventricular filling, reduced LV filling rate both in the first phase of the passive filling and the second phase of active LV filling, increasing E/A ratio of more than 2, significant dilation of the left atrium, as well as positive increase in diastolic reserve that confirms deeper diastolic dysfunction in these adolescents compared with other subgroups.